The Politics History of the Entry of Large Flows of Immigrants Originating from Islamic Countries to the Netherlands - Bethoven Haunt (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This research aims to the Politics History of the Entry of Large Flows of Immigrants Originating from Islamic Countries to the Netherlands Entering the 1990s, the existence of immigrants from Islamic countries began to raise pros and cons. One of the causes of the bad image of Islam in the Netherlands was the assumption that Islam was a lowly religion and culture and was not on par with European culture. A Dutch politician, Frits Bolkestein, who stated that Islam is a religion that often abuses women, besides that governments in Islamic countries implement an authoritarian system and limit the freedom of the population to speak and express opinions. The approach used in writing this research is a qualitative approach and the research basis is a case study and the author uses a descriptive analytical research type. The result show the conflicts that emerged made the Dutch government increasingly worried about the security and social conditions in the country. That's why the government is increasingly tightening the rules for anyone who wants to come to the Netherlands, especially for those who want to settle down or find work there.